If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6n+8/6=-3n+10
We move all terms to the left:
6n+8/6-(-3n+10)=0
We get rid of parentheses
6n+3n-10+8/6=0
We multiply all the terms by the denominator
6n*6+3n*6+8-10*6=0
We add all the numbers together, and all the variables
6n*6+3n*6-52=0
Wy multiply elements
36n+18n-52=0
We add all the numbers together, and all the variables
54n-52=0
We move all terms containing n to the left, all other terms to the right
54n=52
n=52/54
n=26/27
| 6+3k=5k+6 | | 5(13-3x)-17=-5x | | 2p-p-p=0 | | k+18=20 | | 12w=36w | | 9+9^45=x | | 2g+6−14g=−6(g−5)2g+6−14g=−6(g−5) | | Y=5x^2-8x+3 | | 3^(x+1)-2*3^(x-1)=21 | | u/26=4 | | (3x+1)=148 | | m/15=8 | | b+3b+b+3b+2b=360 | | 27g=108 | | 33=20+r | | 54(2x+8)=28(5x-4) | | z/2+6=-77 | | k/3+5=17 | | 6(x-4)=12x | | 16j=480 | | 79°f=1.8+32 | | 28b=980 | | j+53=838 | | 24x-8=20 | | h-180=202 | | 953=n+99 | | 377=s+317 | | p-541=213 | | h+303=694 | | 7y=567 | | 5c+6c-c=130 | | 46=r+40 |